Gender Discrimination in The Bible (Literary Voice, 2025)
Gender Discrimination is a social phenomenon where unfair treatment is meted out to a person based on gender. This inequality is caused due to gender bias or sexism. The treatment may be due to the distinctions with regard to biology, psychology and sociocultural norms. While some of the distinctions are empirically grounded others are social constructs. Gender roles can further lead to unequal treatment. Violence against women is a kind of gender discrimination and can limit their access to education, job opportunities and other facilities thereby perpetuating the cycle of gender inequality.
Keywords: Gender Discrimination, Bible, Women, Christianity, Old Testament